HYPOTHETICAL LEARNING TRAJECTORY IN REALISTIC MATHEMATICS EDUCATION TO IMPROVE THE MATHEMATICAL COMMUNICATION OF JUNIOR HIGH SCHOOL STUDENTS - Ida Nuraida; Asep Amam (IKIP Siliwangi and I-MES, 2019)
This research was motivated by the difficulties of junior high school students in linear equation system material. The focus of this research is to produce the Hypothetical Learning Trajectory (HLT) system of linear equations based on the development of Learning Trajectory (LT) with the aim of research to improve students' mathematical communication skills. Research method used design Research with 3 phases: Preliminary design, teaching experiment, and retrospective analysis. The subject of study in SMP grade VII in Tasikmalaya district. This research uses the instrument of communication skills test students. Processing of research data using test-T. Based on the results of the research obtained: (a) HLT results from the development of LT linear alignment system in RME to improve student mathematical communication skills; and (b) students who acquire RME learning have increased mathematical communication skills greater than those who acquire conventional learning.